Development prospects for production of filtration equipment in the Russian Federation at the present stage - S. S. Gordeev (Вестник университета, 2024)
The article examines the challenges caused by changes in the global situation that the production of filtration equipment faced. The equipment is used for the petrochemical complex. The article assesses prospects for technological independence in the petrochemical complex, including the auxiliary market of filtration and separation equipment. The article provides a statistical analysis of the indicators of the Russian filtration sector and analyses the applied filtration and separation methods in a comparative manner. To determine the prospects of companies producing the corresponding equipment and its individual structural elements, the method of situational analysis was used, with the help of which the features of products manufactured at the present stage that influence the development of business in this economic segment are identified. With the method of economic forecasting, the perspective position of domestic manufacturers in the filtration market was determined. With consideration to the modern developments in the field of industry management and to the given basic concepts used in the management of western companies, the possible ways of introduction of advanced managerial decisions were proposed. It is done in order to improve the position of domestic producers, to develop business and to switch to a new level of product improvement, process optimisation, continuous development of companies’ approaches, and thus respond quickly to the emerging challenges.